2000
DOI: 10.1021/tx990160s
|View full text |Cite
|
Sign up to set email alerts
|

Stress- and Growth-Related Gene Expression Are Independent of Chemical-Induced Prostaglandin E2 Synthesis in Renal Epithelial Cells

Abstract: Cellular stress can initiate prostaglandin (PG) biosynthesis which, through changes in gene expression, can modulate cellular functions, including cell growth. PGA(2), a metabolite of PGE(2), induces the expression of stress response genes, including gadd153 and hsp70, in HeLa cells and human diploid fibroblasts. PGs, gadd153, and hsp70 expression are also influenced by the cellular redox status. Polyphenolic glutathione conjugates retain the ability to redox cycle, with the concomitant generation of reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
2
19
0
1
Order By: Relevance
“…Burns et al [36] also reported that EGF dramatically increased endogenous epoxyeicosatrienoic acid levels in primary cultures of rabbit PTCs. Although the activity of cyclooxygenase is very low in proximal tubule [37], it may be sufficient to have conversion of AA into its metabolites, based upon several reports including our report [38,39]. Indeed, EGF increased PGE 2 , major metabolites of cyclooxygenase, production in this system [unpubl.…”
Section: Discussionmentioning
confidence: 67%
“…Burns et al [36] also reported that EGF dramatically increased endogenous epoxyeicosatrienoic acid levels in primary cultures of rabbit PTCs. Although the activity of cyclooxygenase is very low in proximal tubule [37], it may be sufficient to have conversion of AA into its metabolites, based upon several reports including our report [38,39]. Indeed, EGF increased PGE 2 , major metabolites of cyclooxygenase, production in this system [unpubl.…”
Section: Discussionmentioning
confidence: 67%
“…In inflammatory disease of the kidney, PGE 2 and its receptors are shown to be upregulated (26). In proximal tubule cells from pigs and humans, PGE 2 is generated by reactive oxygen species (27,54) induced by stress and may directly contribute to renal lesions and loss of kidney function. Inasmuch as basolateral uptake is the rate-limiting step of organic anion secretion, we expect that PGE 2 induces stimulation of organic anion secretion into the proximal tubular lumen.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that renal cortex tissue (42), renal epithelial cell lines (43), and isolated proximal tubules (44) produce PGE 2 . The fact that inhibition of COX diminishes organic anion uptake in the OK cell system alone is, of course, not the final proof for EGF-stimulated PGE 2 formation.…”
Section: Discussionmentioning
confidence: 99%